2012
DOI: 10.1103/physrevc.86.064305
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic properties of100Mo: Experimental results and theoretical description of quadrupole degrees of freedom

Abstract: The Coulomb excitation experiment to study electromagnetic properties of the heaviest stable Mo isotope, 100 Mo, was performed using a 76 MeV 32 S beam from the Warsaw cyclotron U-200P. Magnitudes and relative signs of 26 E1, E2, E3, and M1 matrix elements coupling nine low-lying states in 100 Mo were determined using the least-squares code GOSIA. Diagonal matrix elements (related to the spectroscopic quadrupole moments) of the 2 + 1 , 2 + 2 , and 2 + 3 states as well as the 4 + 1 state were extracted. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
143
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(157 citation statements)
references
References 46 publications
(134 reference statements)
14
143
0
Order By: Relevance
“…10. These results were obtained in safe Coulomb excitation experiments of 100 Mo [42] and 94,96 Kr [4] or determined in the present work. The results for the first 2 + states in all nuclei are consistently low.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…10. These results were obtained in safe Coulomb excitation experiments of 100 Mo [42] and 94,96 Kr [4] or determined in the present work. The results for the first 2 + states in all nuclei are consistently low.…”
Section: Discussionsupporting
confidence: 70%
“…The obtained transitional quadrupole moment of the prolate state, Q spins [42]. An inverse trend is observed for 102 Mo, interpreted as a rotational-to-vibrational transition at high spin.…”
Section: Discussionmentioning
confidence: 71%
“…If the ground state of 96 Zr was taken as the pure spherical configuration, the NME becomes 5.64 (PC-PK1) and 3.94 (D1S), respectively. We note that the consideration of higher-order deformation in nuclear wave functions, such as octupole deformation in 150 Sm-Nd [58,59], and triaxiality in 76 Ge-Se [52,53] and 100 Mo-Ru [60], is expected to hinder the corresponding NMEs further in the DFT calculation. Table III lists the upper limits of the effective neutrino mass m ββ based on the present calculated NMEs for the nuclei whose lower limits of the half-life T 0ν 1/2 for the 0νββ-decay have been recently measured [9,10,[61][62][63][64].…”
Section: Sph+pnp (Pc-pk1)mmentioning
confidence: 99%
“…These results can be analyzed in terms of the quadrupole deformation parameters, Q and δ, which are universal variables of quadrupole collective models within the General Bohr Hamiltonian (GBH) [27]. Using the quadrupole sum rules approach [28][29][30][31] the quadrupole invariants, hQ 2 i and hQ 3 cosð3δÞi, can then be obtained. Invariants describe the charge distribution of a nucleus in a given nuclear state.…”
mentioning
confidence: 99%
“…3: the sum of squared E2 matrix elements (SSM) related to hQ 2 i and the sum of triple products of E2 matrix elements (STM) related to hQ 3 cosð3δÞi. The quadrupole invariants can be further related to the GBH collective model variables [31], β (overall deformation parameter) and γ (nonaxiality parameter). It can be concluded that the ground states of the even-even mercury isotopes are weakly deformed with a β value close to 0.15 and are consistent with an oblatelike deformation [hcosð3δÞi ≃ −1], while the excited 0 þ states are more deformed.…”
mentioning
confidence: 99%